Peran Kepemimpinan Kepala Sekolah Dalam Mewujudkan Merdeka Belajar Di Sekolah Dasar (Sd) Mathias III Langgur A, Maluku Tenggara - Meci, Lodovika (Jurnal Ilmiah Wahana Pendidikan, 2024)
In Indonesia, teachers' ability to undertake research is still below average. The Leadership Role of the Principal in Realizing Freedom of Learning at Mathias III Langgur A Elementary School, Southeast Maluku Regency. The purpose of this study was to determine the leadership role of the school principal in realizing Freedom of learning. This study uses a qualitative approach method. The results of the research show that, a) educators; school principals are able to show exemplary figures, motivate, pay attention to teacher welfare, pray together, advise, and visit families. b) manager; the principal is able to realize all school resources. For example; designing, implementing school programs, delegating tasks, attending trainings, conducting evaluations with open communication and mutual trust. This ability is not enough supported by existing facilities and infrastructure. c) administration; school principals are able to compile school programs, financial administration, design learning, and administration classes. d) supervisor; school principals are able to supervise administrative, clinical, monitoring, assessing, and fostering teachers. e) leader; the principal understands enough about the concept of freedom of learning so that he is able to mobilize all stakeholders’ schools, socialize, build commitment in realizing freedom of learning. Based on the results of this study, the role of the principal is very important in realizing Freedom of learning.